Simulated Impact of Vitamin A Fortified Sugar on Dietary Adequacy and Association of Usual Sugar Intake With Plasma and Breast Milk Retinol Among Lactating Women in Rural Zambia. (7th June 2021) - Woldegebreal, Demewoz; Engle-Stone, Reina; Caswell, Bess; Luo, Hanqi; Dodd, Kevin; Arnold, Charles; Jobarteh, Modou; Haskell, Marjorie; Palmer, Amanda
Abstract: Objectives: Zambia introduced mandatory sugar fortification with vitamin A (VA) in 1998; however, regulatory monitoring and evaluation have been limited. We studied the contribution of VA-fortified sugar intake to dietary adequacy, and examined associations between usual sugar and VA intakes with plasma and breast milk retinol concentrations in lactating women in rural Zambia. Methods: We conducted three 24-h dietary recalls among each of 255 lactating women enrolled in a randomized trial, at the time of baseline venous blood and breast milk collection. We measured retinol in biospecimens using high-performance liquid chromatography. We simulated VA intake under various sugar fortification scenarios: 3.1 and 8.8 mg/kg (measured median fortification levels of VA in sugar from previous studies), 10 mg/kg (minimum legal requirement) and 15 mg/kg (minimum legal requirement at factory level). Usual intake distributions, prevalence of inadequate VA intake (< Estimated Average Requirement of 900 μg RAE/d) and prevalence of retinol intake above the tolerable upper intake level (UL, >3000 μg/d) for each scenario were estimated using the National Cancer Institute (NCI) method. We applied the NCI's "bivariate model" as a regression calibration tool to examine associations of usual intake of sugar and dietary VA with plasma and breast milk retinol concentrations. Results: In the absence of sugar fortification, the prevalence of VA inadequacy was predicted to be 83% (SE: 6). Fortification of sugar with VA at 3.1 mg/kg, 8.8 mg/kg, 10 mg/kg and 15 mg/kg would reduce the prevalence of VA inadequacy by 7 (SE:6), 24 (SE:14), 30 (SE:15) and 47 (SE:18) percentage points, respectively, without increasing the risk of retinol intake above the UL. Usual sugar intake and usual VA intake were not associated with plasma retinol or breastmilk retinol concentrations. Conclusions: The sugar fortification program has the potential to reduce dietary VA inadequacy, but the impact is likely to be limited if actual fortification levels are lower than mandated levels. Even if target fortification levels are achieved (10 mg/kg), sugar fortification alone is unlikely to eliminate dietary VA inadequacy among lactating women in rural Zambia. Funding Sources: HarvestPlus and the Sight and Life Global Nutrition Research Institute at Johns Hopkins University.